The result of prospective evaluation of 3-dimensional printing–aided extensive thoracoabdominal aorta repairCentral MessagePerspective - Sung Jun Park, MD, PhD; Jin Kyung Kim, MD; Hong Rae Kim, MD, PhD; Taehun Kim, MS; Sangwook Lee, MS; Guk Bae Kim, PhD; Dong Hyun Yang, MD, PhD; Joon Bum Kim, MD, PhD (JTCVS Techniques)
Objectives: Paraplegia is a distressing complication after open thoracoabdominal aortic aneurysm (TAAA) repair, and revascularization of T8-L2–level segmental arteries is considered pivotal to prevent paraplegia. We employed 3-dimensional (3D) printing to efficiently revascularize segmental/visceral arteries and prospectively evaluated its safety and efficacy. Methods: From January 1, 2020, to June 30, 2022, we prospectively enrolled patients of extent I, II, or III TAAA repair. Guidance models were 3D-printed based on preoperative computed tomography, and multibranched aortic grafts were manually constructed upon this model before surgery. The composite outcome of operative mortality, permanent stroke, and permanent spinal cord deficit (SCD) was compared with the historical control group (n = 77, in 2015-2020), subjected to similar TAAA repair without 3D printing. Results: A total of 38 patients (58.6 ± 13.2 years) underwent open TAAA repair with the aid of 3D printing. Extent I, II, and III repairs were performed in 14 (36.8%), 17 (44.7%), and 7 (18.4%), respectively. Concomitant arch repair and bi-iliac reconstruction were performed in 7 (18.4%) and 6 patients (15.8%), respectively. Mean pump time was 107.7 ± 55.5 minutes. Operative mortality, permanent stroke, and permanent SCD each occurred in 1 patient (2.6%), and the incidence of the composite outcome was 7.9% (3/38). In the control group, mean pump time was 166.0 ± 83.9 minutes, significantly longer than the 3D-printing group (P < .001), and operative mortality, permanent stroke, permanent SCD, and the composite outcome occurred in 7 (9.1%), 9 (11.7%), 8 (10.4%), and 19 (24.7%), respectively. Conclusions: Open repairs of extensive TAAA with 3D printing showed favorable safety and efficacy, which need further validation by larger studies.